Characterization of Integrons and Resistance Genes in Salmonella Isolates from Farm Animals in Shandong Province, China - Zhao, Xiaonan; Yang, Jie; Zhang, Baozhen; Sun, Shuhong; Chang, Weishan (Frontiers in Microbiology, 2017)
A total of 154 non-duplicate Salmonella isolates were recovered from 1,105 rectal swabs collected from three large-scale chicken farms (78/325, 24.0%), three large-scale duck farms (56/600, 9.3%) and three large-scale pig farms (20/180, 11.1%) between April and July 2016. Seven serotypes were identified among the 154 isolates, with the most common serotype in chickens and ducks being Salmonella enteritidis and in pigs Salmonella typhimurium. Antimicrobial susceptibility testing revealed that high antimicrobial resistance rates were observed for tetracycline (72.0%) and ampicillin (69.4%) in all sources. Class 1 integrons were detected in 16.9% (26/154) of these isolates and contained gene cassettes aadA2, aadA1, drfA1-aadA1, drfA12-aadA2, and drfA17-aadA5. Three β-lactamase genes were detected among the 154 isolates, and most of the isolates carried blaTEM-1 (55/154), followed by blaPSE-1 (14/154) and blaCTX-M-55 (11/154). Three plasmid-mediated quinolone resistance genes were detected among the 154 isolates, and most of the isolates carried qnrA (113/154), followed by qnrB (99/154) and qnrS (10/154). Fifty-four isolates carried floR among the 154 isolates. Multilocus sequence typing (MLST) analysis showed that nine sequence types (STs) were identified; ST11 was the most frequent genotype in chickens and ducks, and ST19 was identified in pigs. Our findings indicated that Salmonella was widespread, and the overuse of antibiotics in animals should be reduced considerably in developing countries.